Analysis of the morphology of retinal vascular cells in zebrafish (Danio rerio) - Middel, Chiara Simone; Dietrich, Nadine; Hammes, Hans-Peter; Kroll, Jens (Frontiers in Cell and Developmental Biology, 2023)
Background: Zebrafish (Danio rerio) have been established in recent years as a model organism to study Diabetic Retinopathy (DR). Loss of endothelial cells and pericytes is an early hallmark sign developing DR in the mammalian retina. However, morphology, numbers, ratios, and distributions of different vascular cells in the retinal compartment in zebrafish have not yet been analyzed and compared with the mammalian retina.Methods: The retinal trypsin digest protocol was established on the zebrafish retina. Cell types were identified using the Tg(nflk:EGFP)-reporter line. Cells were quantified using quantitative morphometry.Results: Vascular cells in the zebrafish retina have distinct morphologies and locations. Nuclei of vascular mural cells appear as long and flat nuclei located near the vessel wall. Round nuclei within the vessel walls can be identified as endothelial cells. The vessel diameter decreases from central to peripheral parts of the retina. Additionally, the numbers of vascular cells decrease from central to peripheral parts of the retina.Discussion: The retinal trypsin digest protocol, which can be applied to the zebrafish retina, provides novel insights into the zebrafish retinal vascular architecture. Quantification of the different cell types shows that, in comparison to the mammalian retina, zebrafish have higher numbers of mural cells and an increased mural cell to endothelial cell ratio. This protocol enables to quantify mural cell and endothelial cell numbers, is easily adaptable to different transgenic and mutant zebrafish lines and will enable investigators to compare novel models on a single cell level.